New Fraud Diamond dan Deteksi Kecurangan Financial Statement pada Perusahaan Manufaktur Yang Terdaftar Di ISSI - Rosyid Nur Anggara Putra; Cici Nurmayang Sari (Jurnal Akuntansi dan Audit Syariah)
Financial statement fraud is an intentional act by certain parties in manipulating financial numbers on financial statements so that the disclosure of information is not appropriate. To detect such fraud, several approaches can be taken through financial target, nature of industry, earnings growth, and change in directors. The purpose of this study is to examine the influence of the new fraud diamond model on financial statement fraud as measured by the Beneish M-Score model. The population in this study uses manufacturing companies listed on the Indonesian Sharia Stock Index (ISSI) from 2018-2021. In selecting the sample for this study, purposive sampling techniques were used in accordance with the research criteria, resulting in 20 companies with 80 research data. Data analysis techniques use panel data regression with the help of Microsoft Excel software and E-views statistical tool version 12. The results of this study indicate that financial target, nature of industry, and change in directors do not have a significant effect on financial statement fraud, while earnings growth has a negative and significant effect on financial statement fraud. Therefore, this study can be said to support the new fraud diamond model in financial statement fraud.